Participatory Ergonomics in Industrially Developing Countries: A Literature Review - Prayitnoadi R, Priyoko; Lawson, Glyn; Hermawati, Setia; Ryan, Brendan (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2021)
Participatory ergonomics (PE), the origins of which can be traced back to the western ergonomics approach, is an approach that focuses on involving workers to improve safety and health at their workplace. This paper has presented a literature review of studies concerning PE, the methodological approaches used to study PE and PE in industrial developing countries (IDCs). The paper has also explained factors which would seem to pose an extra challenge in applying PE in IDCs and Indonesia. The purpose of this was to provide the reader with a view of how the development of participatory ergonomics today possibly can help solve the problem of occupational safety in small-medium size enterprises (SMEs) in Indonesia.